PENINGKATAN RESILIENSI TERHADAP PERKEMBANGAN TEKNOLOGI DIGITAL PADA SISWA SDN 2 NGESREP MELALUI PROGRAM KKN EDUKATIF - Putri, Revania Galdis Dewanti; Jasandria, Febia Sukma; Apriliani, Vierla Mariska; Priadythama, Ilham (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The rapid development of digital technology has impacted the learning and play patterns of elementary school students. At SDN 2 Ngesrep, excessive gadget use has led children to become more familiar with digital games than with physical and traditional activities, leading to a decline in social interaction and motor skills. Furthermore, arts instruction in schools remains limited to theory, thus suboptimal opportunities for students' creative exploration. In response, the Community Service Program (KKN) was implemented with the aim of reviving traditional games as a means of character building, practicing environmentally friendly art skills through eco-printing, and introducing tie-dye batik as a form of local cultural preservation. This activity involved 20 students from grades IV-VI, with KKN students acting as facilitators, mentors, and agents of change. The results showed increased student enthusiasm, artistic creativity, motor skills, and resilience to the negative impacts of digital technology development.